a a a a + + + b b b b + + + + c c c c + + + + d d d d = = = = = 3 4 5 6 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This should be level 1.
Log in to reply
It now is. New problems sometimes take a while to stabilize in their level.
Step 1
a + b + c + d = x
When a is removed, the equation is equal to 6.
When b is removed, the equation is equal to 5.
When c is removed, the equation is equal to 4.
When d is removed, the equation is equal to 3.
Therefore, b = a + 1 , c = b + 1 , and d = c + 1
Step 2
6 = b + ( b + 1 ) + ( b + 2 )
Simplify
6 = 3 b + 3
-3
3 = 3 b
Divide by 3
1 = b
Step 3
a = b - 1 therefore a = 0
b = b therefore b = 1
c = b + 1 therefore c = 2
d = b + 2 therefore d = 3
Step 4
0 + 1 + 2 + 3 = 6
Good observation in step 1. Taking the difference.
If we examine the formulas, we can see that if we combine the first three equations, then we will get the next formula here:
3 ( a + b + c + c ) = 3 a + 3 b + 3 c + 3 d = 1 8
We can then see that the final equation is equal to the sum of all of the different variables, we can divide both sides by 3 to find the final value. We don't need to find the values of the individual variables so we simply carry out this operation to get the answer.
3 a + 3 b + 3 c + 3 d = 1 8
3 3 a + 3 b + 3 c + 3 d = 3 1 8
a + b + c + d = 6
Good observation :)
Avoid any calculations by just paying attention to the possible answers - if b+c+d=6 then all answers below 6 are automatically excluded as possible solutions. ;)
Well, the a term could be negative.
Problem Loading...
Note Loading...
Set Loading...
Adding first four equations we get 3 ( a + b + c + d ) = 1 8 ⇒ a + b + c + d = 6 .